PROGESTERONE PROFILE IN TWO DIFFERENT PROTOCOLS OF ESTRUS SYNCHRONIZATION IN POST PARTUM RED KANDHARI COWS - DESHMUKH, Y D; MARKANDEYA, N M; CHAUDHARl, R J; DESHMUKH, V V (The Indian Journal of Animal Reproduction, 2023)
Thirty six post-partum Red Kandhari cows were selected and randomly divided into two groups i.e. protocolgroup I (Select synch) and Protocol Group-II (Ovsynch) comprising twelve animals each and control Groups Ill andIV comprising six animals each. Protocol group animals were administered with injection GnRH 1 00μgintramuscularly on day 1st followed by injection PGF2 526μg intramuscularly on day 7th. Second injection ofGnRH 100μg was administered intramuscularly only in protocol group II on day 91h and after 16-22 hrs of secondGnRH injection, fixed time inseminations were carried out whereas in protocol group I, animals confirmed in estruswere bred by Al at appropriate times. The mean serum progesterone level of cows on day 1•1, 71ti, 91h and 19th of thetrial in protocol group I was 01.80, 02.90, 01.10, 04.20 and in protocol group ll the same was 01.90, 03.60, 01.10and 06.84 ng/ml on day 1 •t, 71\ 9t11and19'h whereas in control groups iii and IV, the level was 2.5, 2.4, 2.3, 2.4 and2.5, 2.4, 2.3, 2.5 ng/ml respectively. The difference in the level of progesterone was non-significant throughout theexperiment in control group animals. Selectsynch protocol in Red Kandhari cows was effective to induce estruswith 66.67 per cent efficacy and 87.50 per cent conception rate and 58.33 per cent pregnancy rate, whereasovsynch protocol was successful to induce estrus with 66.67 per cent efficacy with 50.00 per cent conception rateand pregnancy rate.
Keywords: Estrus $ynchronization; Red Kandhari; Cows